Why Do Students Need to Establish Ecoliteracy? - Noviana, Eddy; Supentri, Supentri; Hidayati, Rahmatul; Huda, Muhammad Nailul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
This survey research aimed at determining the ecological intelligence level of students. It involved 120 fourth grade students of elementary school. The findings revealed that the students’ intelligence level, with an average score of 77.48, was classified in ‘high’ category. In addition, other aspects were also classified into the ‘high’ category with an average score on attitude aspect of 78.19, skill aspect of 77.69, and participation aspect of 76.56. To conclude, the ecological intelligence of the fourth grade elementary school students was classified in ‘high’ category.